2017
DOI: 10.1021/acs.est.7b03333
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Tracking of Copper-64 Radiolabeled Nanoparticles in Lactuca sativa

Abstract: Engineered nanoparticles (NPs) are increasingly used in commercial products including automotive lubricants, clothing, deodorants, sunscreens, and cosmetics and can potentially accumulate in our food supply. Given their size it is difficult to detect and visualize the presence of NPs in environmental samples, including crop plants. New analytical tools are needed to fill the void for detection and visualization of NPs in complex biological and environmental matrices. We aimed to determine whether radiolabeled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…The combined use of 2-D (DF-HSI) and 3-D (nano-CT) techniques provides better means to characterize and evaluate the NPplant interaction at the cellular level (Avellan et al, 2017). Another non-invasive, highly sensitive method to visualize NPs through the combination of autoradiography, positron emission tomography (PET)/CT, TEM, and SEM was demonstrated in lettuce (Lactuca sativa) (Davis et al, 2017). In a pioneering study, the effect and interaction of TiO 2 NPs with garlic (Allium sativum) was observed through spectroscopic techniques using time-resolved, laser-induced fluorescence and ultravioletvisible spectra.…”
Section: Methods To Study Uptake Quantification and Translocation Omentioning
confidence: 99%
“…The combined use of 2-D (DF-HSI) and 3-D (nano-CT) techniques provides better means to characterize and evaluate the NPplant interaction at the cellular level (Avellan et al, 2017). Another non-invasive, highly sensitive method to visualize NPs through the combination of autoradiography, positron emission tomography (PET)/CT, TEM, and SEM was demonstrated in lettuce (Lactuca sativa) (Davis et al, 2017). In a pioneering study, the effect and interaction of TiO 2 NPs with garlic (Allium sativum) was observed through spectroscopic techniques using time-resolved, laser-induced fluorescence and ultravioletvisible spectra.…”
Section: Methods To Study Uptake Quantification and Translocation Omentioning
confidence: 99%
“…The application of positron imaging to plant studies has increased significantly since the initial water transport analyses by McKay et al 2 While dynamics of water movement with PET in plants has been widely studied, [25][26][27][28][29][30][31][32][33][34][35] other topics related to PET have increasingly been investigated, including uptake and translocation of nutrients, [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]98,99 photoassimilate fixation/allocation, 15,22,23, sugar transport, 21,[82][83][84][85][86][87] and heavy metal contaminant uptake and transport 25,[88][89][90][91][92][93]…”
Section: Physics Of Positron Detection In Plant and Soil Systemsmentioning
confidence: 99%
“…Davis et al used autoradiographic, PET/CT, and electron imaging approaches to study the uptake and translocation of functionalized, nanoparticulate [ 64 Cu]CuO by lettuce (Lactuca sativa). 88 Nanoparticles were observed to enter seedlings through the roots, where much of the 64 Cu accumulated, with some subsequent translocation to cotyledons. Dosing concentration of nanoparticles did not impact translocation within lettuce seedlings, but nanoparticle size did, with greater amounts of smaller (% 10 nm) nanoparticles taken up over a longer period of time relative to larger particles (% 20 nm).…”
Section: Positron Imaging For Visualization Of Plant Uptake and Translocation Of Phytotoxic Metalsmentioning
confidence: 99%
“…Similarly, the isothiocyanate‐functionalised TACN derivatives 45 , 50 – 54 , and 65 can be linked to amino‐terminated biomolecules via highly stable thiourea bonds . Over the last decade, “clickable” versions of BFCAs have also been used for tagging different biomolecules and nanoparticles to allow PET imaging using 64 Cu . Examples of these include ligands 55 , 56 and 60 for rapid conjugation to specific peptides by Cu I ‐catalysed click reaction, and strained cyclooctynes 57 – 59 for copper‐free attachment to azide‐functionalised peptides, proteins and nanoparticles.…”
Section: Radiopharmaceutical Chelatesmentioning
confidence: 99%
“…Over the last decade, “clickable” versions of BFCAs have also been used for tagging different biomolecules and nanoparticles to allow PET imaging using 64 Cu . Examples of these include ligands 55 , 56 and 60 for rapid conjugation to specific peptides by Cu I ‐catalysed click reaction, and strained cyclooctynes 57 – 59 for copper‐free attachment to azide‐functionalised peptides, proteins and nanoparticles. Also, tetrazine‐bearing NOTA derivatives 61 and 62 have been used for linking trans ‐cyclooctene‐functionalised antibodies using inverse‐electron‐demand Diels–Alder reactions …”
Section: Radiopharmaceutical Chelatesmentioning
confidence: 99%